Urinary Catheter-Associated Microbial Colonization in Libya: Microbial Profile, Antimicrobial Resistance, and Challenges in Empirical Treatment - Tahani Nsair; Tarek Gibreel; Elloulu BenDarif; Amal Ben Drief; Mouna Elgadhafi; Haytham Al-Salimi; Bashir Nsair; Marwa Gamra (AlQalam Journal of Medical and Applied Sciences, 2026)
Catheter-associated bacteriuria (CAB) is one of the most frequent healthcare-associated infections (HAIs), particularly in critically ill patients, where indwelling urinary catheters are commonly used. This prospective cross-sectional study aimed to assess the microbial colonization profile and evaluate antimicrobial resistance (AMR) and antibiotics usage patterns among patients admitted to medical and surgical intensive care units (ICUs) at Maitega Military Hospital in Tripoli, Libya. A total of 100 urinary catheters, removed from patients aged over 18 years and inserted for at least 24 hours, were collected and analyzed. Catheter tips were aseptically processed, sonicated to release biofilm-associated bacteria, and cultured on various selective and non-selective media. Microbial identification and antibiotic susceptibility testing were performed according to Clinical and Laboratory Standards Institute (CLSI) guidelines using the Kirby-Bauer disk diffusion method. Data collected included demographics, clinical history, and details concerning the type and duration of catheterization. All catheters showed evidence of microbial colonization, with a total of 114 isolates obtained, representing 17 microbial species. Escherichia coli was the most frequently isolated organism (20.2%), followed by Pseudomonas aeruginosa (12.3%), Pantoea spp. (8.8%). Notably, several isolates exhibited multidrug resistance (MDR), particularly among Gram-negative bacteria, and ESBL production was detected in a significant subset of E. coli and Klebsiella species isolates. Statistical analysis revealed that catheter duration was significantly longer in ICU patients compared to other departments (p=0.034). Out of 26 factors analyzed, five independent risk factors were identified for colonization with ESBL-producing Gram-negative bacteria: a prior UTI diagnosis, previous treatment with third-generation cephalosporins, a history of diabetes mellitus, and bacterial resistance to fluoroquinolones and nitrofurantoin. This study highlights the widespread colonization of urinary catheters and the high prevalence of antibiotic-resistant organisms in ICU settings. The findings underscore the critical need for rigorous infection control practices, routine surveillance of catheter-associated infections, and the implementation of targeted antimicrobial stewardship programs.